Self-esteem people with HIV/AIDS: Review of reality counseling approach - Anis Lud Fiana (Fakultas Dakwah dan Komunikasi UIN Walisongo, 2020)
Purpose - The purpose of this study was to determine the self-esteem of people with HIV/AIDS in terms of the reality counseling approach.Method - The method used in this paper is a literature study.Result - The results of this study indicated that the reality counseling approach with the wants, needs, and perceptions, direction and doing, self-evaluation, and planning (WDEP) technique could help their circumstances and situations assess more realistically, help reduce the burden on thoughts, help find meaning in their lives, help have a life expectancy, and maintain or increase the self-esteem of people with HIV/AIDS.Implications - The results of this study expected to provide benefits in scientific guidance and counseling considering that in terms of applicability, the reality approach can be used for various problems in counseling practice.Originality - In this paper, a reality counseling approach can be one way as a form of mental support. People with HIV/AIDS needs the help of others in going through its downtime in achieving the self-esteem that ultimately reaches the meaning of his life. Tujuan - Tujuan penelitian ini adalah untuk mengetahui harga diri orang dengan HIV/AIDS (ODHA) ditinjau dari pendekatan konseling realitas.Metode - Metode yang digunakan dalam penulisan ini adalah studi literatur.Hasil - Hasil penelitian ini menunjukkan bahwa pendekatan konseling realitas dengan teknik wants, needs, and perceptions, direction and doing, self-evaluation, and planning (WDEP) dapat membantu menilai keadaan dan situasi mereka secara lebih realistis, membantu mengurangi beban pikiran, membantu menemukan makna dalam hidup mereka, membantu memiliki harapan hidup, dan mempertahankan atau meningkatkan harga diri ODHA.Implikasi - Hasil penelitian ini diharapkan dapat memberikan manfaat dalam bidang bimbingan dan konseling, pendekatan realitas dapat digunakan untuk berbagai permasalahan dalam praktik konseling.Orisinalitas - Dalam tulisan ini, pendekatan konseling realitas dapat dijadikan salah satu bentuk dukungan mental. ODHA membutuhkan bantuan orang lain dalam menjalani masa henti dalam mencapai harga diri yang pada akhirnya mencapai makna hidupnya.